Transformational, Transactional Leadership, and Perceptions of Organizational Performance: The Moderating Role of Relational Authenticity as a Leader - Min Hyu Kim (Transylvanian Review of Administrative Sciences, 2022)
This study examines whether relational authenticity as a leader, a relatively new concept in the nonprofit literature, moderates the relationship between transformational, transactional leadership, and perceptions of organizational performance. Using an online survey experiment of executive directors at 403 nonprofit organizations, this study tests the hypothesis of the positive–negative asymmetry effects, which states that negative impressions are more impactful than positive ones. The findings illustrate that, in the case of positive personal behavior, a transformational leader (vs. transactional leader) acting favorably has a statistically significant positive influence on organizational performance. However, in the case of negative personal behavior, the treatment had null findings. This study suggests that nonprofit leaders should pay attention to achieving relational authenticity as a leader to ensure the sustainability of transformational leadership effects.